Negotiating precarious online spaces for enhanced gender equality: challenges and opportunities for Zimbabwean gender advocacy - Makwembere, S.; Tambo, B. (International Conference on Public Administration and Development Alternatives (IPADA), 2017)
Social, economic and political challenges since the 2000s have especially propelled the need for civic action to challenge gender inequality issues. The emphasis of political reforms, for example, placing restrictions on public gatherings through the Public Order and Security Act, has created constraints for civic action around these matters. In recent years, while the formation of women movements has not been restricted, they have had to exercise an ability to adapt under what might be considered as unfavourable advocacy situations. Citizen movements which had generally almost disappeared from Zimbabwe’s body politics after the 2013 general elections, appear to have reawakened through hashtag movements which use social media to break the restrictions on political mobilisation in the physical political space. The mobilisation and protests seen through social media symbolise a new frontier of activism and collective mobilisation. Where the hashtag movements have translated online mobilisation into street demonstrations, this reveals the potential influence of social media in politics. It is recognised that women generally play a peripheral role in citizen movements and part of the challenge is that the new movements forming via social media need to be interrogated to see if they are adequate spaces for women participation and gender equality dialogue. This paper seeks to unpack the challenges and opportunities of online gender advocacy through social media in Zimbabwe. Considering the recognised importance of broadening the representation of women in governance processes, the paper contributes to discussions on the influences of current online modes of civic action on gender equality.
Journal article, Published in International Conference on Public Administration and Development Alternatives (IPADA), The 2nd Annual Conference on ‛‛ The Independence of African States in the Age of Globalisation”, July 26-28, 2017
Keywords: Gender equality; Hashtag movements; New media activism; Social media; Women movements; Sex discrimination -- Zimbabwe; Online social networks; Social media; Feminisim -- Zimbabwe